Pentingnya Kemampuan Bahasa Inggris dalam Menghadapi Globalisasi di Panti Asuhan Menara Kasih Indonesia Kota Medan - Muhammad Fadhlan Amri; Agus Suriadi (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Globalization is a situation that will be faced by almost all countries, including Indonesia. And globalization will certainly have an impact on all people from various walks of life and backgrounds, including orphanages. In addition, the main problem of orphanages in general is how the survival and ability of the orphans after graduating from high school level and the lack of skills they have, especially for children in the Menara Kasih Indonesia Orphanage, Medan City. The output target to be achieved is the formation and improvement of children who have values ​​and the ability to speak English in their preparation to face globalization. The solution offered in this Field Work Practice activity is group learning by introducing and inculcating the benefits of the importance of English, as well as teaching various basic materials from English. And also in this activity, holding a mini project, which will solve the problem of one of the clients at the Menara Kasih Indonesia Orphanage, using the Casework method which consists of 5 stages namely Engagement, Intake and Contract, then Assessment, then Program Planning, then Intervention, and ends with Evaluation and Termination.